2023
DOI: 10.3389/fpls.2023.1170641
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association and epistasis studies reveal the genetic basis of saline-alkali tolerance at the germination stage in rice

Abstract: IntroductionSaline-alkali stress is one of the main abiotic factors limiting rice production worldwide. With the widespread use of rice direct seeding technology, it has become increasingly important to improve rice saline-alkali tolerance at the germination stage. MethodsTo understand the genetic basis of saline-alkali tolerance and facilitate breeding efforts for developing saline-alkali tolerant rice varieties, the genetic basis of rice saline-alkali tolerance was dissected by phenotyping seven germination-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…In the qGRG4 locus, OsHAK1, a well-characterized high-affinity K + transporter that promotes rice seedling growth under salt stress, is present (Chen et al, 2015(Chen et al, , 2018. The OsHAK1 gene was also reported before in the q4.8 locus (Zhang et al, 2023), and is associated with relative germination rate on the 3 rd day under saline-alkali stress. In addition, other HAK genes such as OsHAK12 (Zhang et al, 2021), OsHAK16 (Feng et al, 2019) and OsHAK21 (He et al, 2019;Song et al, 2021) are implicated in salt tolerance in rice.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In the qGRG4 locus, OsHAK1, a well-characterized high-affinity K + transporter that promotes rice seedling growth under salt stress, is present (Chen et al, 2015(Chen et al, , 2018. The OsHAK1 gene was also reported before in the q4.8 locus (Zhang et al, 2023), and is associated with relative germination rate on the 3 rd day under saline-alkali stress. In addition, other HAK genes such as OsHAK12 (Zhang et al, 2021), OsHAK16 (Feng et al, 2019) and OsHAK21 (He et al, 2019;Song et al, 2021) are implicated in salt tolerance in rice.…”
Section: Discussionmentioning
confidence: 70%
“…qGRG3-1 overlaps with the reported 16.66−17.02 Mbp region on chromosome 3, which is associated with shoot fresh weight under salt stress (Yu et al, 2023). qGRG3-2 overlaps with the reported q5.11 locus that is associated with the relative germination rate under saline-alkali stress (Zhang et al, 2023). However, no salt tolerance-related gene has been reported in these regions.…”
Section: Discussionmentioning
confidence: 74%
“…Rice alkalinity tolerance is a complex trait controlled by multiple genes [11]. To date, approximately 182 quantitative trait loci (QTLs) related to alkalinity tolerance have been identified [12][13][14][15][16][17]. Li et al [1] analyzed 295 japonica rice varieties and found that qSNK3-1 (15.0 Mb), which is located on chromosome 3, was correlated with ion homeostasis under salinity-alkalinity stress.…”
Section: Introductionmentioning
confidence: 99%